2007
DOI: 10.1109/tdei.2007.4286513
|View full text |Cite
|
Sign up to set email alerts
|

Invited Paper - Environmental Applications of Repetitive Pulsed Power

Abstract: High repetition rate, high reliability and long lifetime are required for pulsed power generators for environmental applications. Also, it is necessary to optimize the pulsed power generator for each environmental application. Recent developments in pulsed power generators are described. In addition, recent research of gaseous phase pollution control using pulsed power, cleaning of lake and dam of algae bloom by discharges, and recycling of concrete by pulsed power is summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(26 citation statements)
references
References 28 publications
(43 reference statements)
0
26
0
Order By: Relevance
“…Previous studies have demonstrated that the velocity and mode of propagation of the streamer depends on the electric field, which in turn is a function of the applied voltage, with higher voltage levels leading to a reduced time of breakdown in streamer formation [31,32]. For underwater discharge, it has been shown that an increase in peak high voltage results in a higher velocity of streamer propagation [1], an increase in streamer length [12], and a reduction of streamer development time [31]. Real-time images of streamer captured by an ultra-high speed framing camera at applied voltage of (a(i-iv)) 11.6 kV, exposure time 150 ns; and (b(i-iv)) 21.6 kV, exposure time 50 ns; interframe rate 250 ns for both cases (scale bar = 5 mm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the velocity and mode of propagation of the streamer depends on the electric field, which in turn is a function of the applied voltage, with higher voltage levels leading to a reduced time of breakdown in streamer formation [31,32]. For underwater discharge, it has been shown that an increase in peak high voltage results in a higher velocity of streamer propagation [1], an increase in streamer length [12], and a reduction of streamer development time [31]. Real-time images of streamer captured by an ultra-high speed framing camera at applied voltage of (a(i-iv)) 11.6 kV, exposure time 150 ns; and (b(i-iv)) 21.6 kV, exposure time 50 ns; interframe rate 250 ns for both cases (scale bar = 5 mm).…”
Section: Resultsmentioning
confidence: 99%
“…Water surface discharge holds promise as a new and attractive method for environmental applications, such as the degradation of dissolved organic pollutants, sterilization of microorganisms, and the treatment of algae blooms [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, pulsed power applications have been studied for such diverse fields as industry, environment, and bioelectronics, and in tandem, many types of high repetitive pulsed power sources have been developed for multiple applications, each with different output factor such as voltage, current energy, pulse width, and repetitive rate [1][2]. High repetitive pulsed power modulators ranging from severalhundred pps to kpps are especially important for industrial applications that also require low switching loss (stability) and miniaturization of the pulsed power modulator [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…R ECENTLY, considerable studies have been conducted on the environmental applications of pulsed power systems such as water or gas treatment [1]- [6]. Generally, the leachate from sewage-filled ground is treated by chemical or biological methods even though the methods are expensive and require large facilities and extensive treatment time.…”
Section: Introductionmentioning
confidence: 99%
“…By adopting an IGBT which can handle 1200 A for a short time, rising time is limited at 300 ns [14]. However, a rapid rising time of less than 100 ns, a high repetition rate, a relatively short pulse width, and high stability are required for the environmental application [6]. Therefore, in this study, faster rising times (< 100 ns) can be achieved by selecting optimized IGBT characterized by low reverse capacitance.…”
Section: Introductionmentioning
confidence: 99%